Pengembangan Minat dan Bakat Anak yang Berimplikasi Tindak Pidana - Muhammad Mughoni Zakariya (Faculty of Law, Universitas Airlangga, 2022)
Abstract Children are human beings who have a great opportunity to develop their talents, but in extreme cases they also become victims of exploitation. Law must regulate the boundaries between actions in the name of talent development and actions in the name of exploitation. In this paper examines these events with a law approach and conceptual approach. By using the child protection law, the child welfare law, the law on combating trafficking in persons and the law on combating domestic violence to find out the concept of exploitation. Then use the reference to be able to know the boundaries between developing the potential of children's talents with acts of exploitation. Meanwhile, conceptually reviewing the meaning of exploitation itself and analyzing the nature of work that should not be done by children and forms of work that are harmful to children as well applying sanctions based on child protection laws and labor laws that include sanctions can be imposed on perpetrators who exploit children. Keywords: Talent; Developing Children’s Talent; Economics; Child; Responsibilty. Abstrak Anak adalah sosok insan yang sangat berpeluang besar dalam pengembangan bakat, akan tetapi sangat rawan juga menjadi korban eksploitasi. Maka dalam hukum harus mengatur batas – batas antara tindakan yang mengatasnamakan pengembangan bakat dan tindakan yang mengatasnamakan eksploitasi. Dalam penulisan ini mengkaji peristiwa tersebut dengan pendekatan undang – undang dan pendekatan konseptual. Dengan menggunakan undang-undang perlindungan anak, undang-undang kesejahteraan anak, undang-undang pemberantasan tindak pidana perdagangan orang dan undang-undang pemberantasan tindakan kekerasan dalam rumah tangga untuk mengetahui konsep dari eksploitasi. Kemudian menggunakan acuan tersebut untuk dapat mengetahui Batasan-batasan antara mengembangkan potensi bakat anak dengan tindakan eksploitasi. Sementara itu secara konseptual mengkaji mengenai pengertian dari eksploitasi itu sendiri serta menganalisa sifat-sifat pekerjaan yang tidak boleh dilakukan oleh anak dan bentuk bentuk pekerjaan yang berbahaya bagi anak. Serta menerapkan sanksi berdasarkan undang-undang perlindungan anak dan undaang-undang ketenagakerjaan yang mencantumkan sanksi dapat dikenakan bagi pelaku yang mengeksploitasi anak. Kata Kunci: Pengembangan Potensi Anak; Ekonomi; Anak; Pertanggungjawaban.